2022
DOI: 10.3389/fped.2022.859343
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Infection in Asymptomatic Congenital Lung Malformations—A Decade Retrospective Study

Abstract: BackgroundWhether to operate on asymptomatic patients with congenital lung malformations (CLMs) remains controversial. Our study intended to find out the proportion of hidden infection in CLMs and its effect on surgery, to provide help for the management of asymptomatic CLMs patients.MethodsA retrospective review of the medical records of patients with asymptomatic CLMs from January 2011 to December 2020 was performed in our center. Selected asymptomatic patients were divided into a non-hidden infection group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…102 patients underwent resection at age 14 months (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). 80% of children were asymptomatic in the neonatal period and 22% of these went on to develop a respiratory symptom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…102 patients underwent resection at age 14 months (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). 80% of children were asymptomatic in the neonatal period and 22% of these went on to develop a respiratory symptom.…”
Section: Resultsmentioning
confidence: 99%
“…14 The presence of inflammation has been reported on histological examination in up to 50% of resected asymptomatic lesions and is found more frequently with increasing age at time of resection. [15][16][17][18] In asymptomatic lesions, inflammation may be a sequela of subclinical infection but can also be chronic without evidence of infection. 17 Malignancy is reported to have occurred in the setting of CPAMs 19,20 and BCs, 21 and there is an association between chronic inflammation and tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of these symptoms indicates the need for immediate surgical resection, however, the treatment plan for patients with prenatal diagnosis of CPAM who are asymptomatic is less clear. The study by Liu Chenyu et al 7 found that 32% of 581 asymptomatic Congenital Lung Malformations patients had hidden infection(HI) in postoperative pathology, and the proportion of HI was high, which would increase the difficulty and risk of surgery,so early surgery was advocated. Stanton et al 8 , Laberge et al 6 and Esposito et al 9 recommend surgery in patients with congenital lung malformations by the first year of life,and the consensus of experts in China recommend surgery should be performed between 3 months and 1 year old 10 , because patients who undergo early resection are thought to experience compensatory lung growth to reduce the risk of complication,to make the procedure technically easier and decrease radiation exposure and related risks 9,11 .However,some scholars believe that delaying surgery to later in infancy is beneficial as older children have a decreased anaesthetic and surgical risk 12,13 .The primary objective of our systematic review is to evaluate if age at surgical treatment of asymptomatic paediatric CPAM patients is associated with outcomes to determine the optimal age for surgical intervention and optimize treatment.The primary objective of our systematic review was to assess whether age at surgical treatment is associated with outcome in asymptomatic pediatric CPAM patients to determine the optimal age for surgical intervention and optimize treatment.…”
Section: Objectivesmentioning
confidence: 99%
“…Most infants with CPAM are asymptomatic at birth, but symptoms such as fever, cough, pneumothorax and recurrent pneumonia infections may occur later in life [3]. The probability of lung infection increases over time and may have a risk of malignant transformation, which makes surgery more difficult, so early surgery is advocated [4][5][6].…”
Section: Introductionmentioning
confidence: 99%